Neuropathology of phenylketonuria (PKU) - Norma Specola (Instituto Nacional de Pediatría, 2014)
Untreated phenylketonuria (PKU) causes cognitive, neuropsychological and motor skills impairment as well as microcephaly and demyelization. Persistent hyperphenylalaninemia produces toxicity on neurons and glial cells, alters cortical development, growth and dendritic density High levels of phenylalanine and low levels of neutral aminoacids in the brain disrupt neurotransmitter synthesis, increase oxidative damage, reduce the number of dopaminergic neurons and decrease the length of dendrites. White matter lesions are not present in all patients and there is no relation between these lesions and clinical severity. It has been shown that selenium and carnitine supplementation can decrease lipid and protein peroxidation. There are several mechanisms involved in neurodegeneration of patients with phenylketonuria; early treatment and strict nutritional control significantly improve the prognosis of these patients.